H-ZSM-11 and Zn-ZSM-11 zeolites and their applications in the catalytic transformation of LDPE - Renzini, Maria Soledad (2009)
Low density polyethylene was converted into hydrocarbons over Zn- and H-ZSM-11 zeolite catalysts in a fixed-bed reactor during 20 and 60 min reaction time, 0.5 and 2.0 polymer to catalyst mass ratio at 500 °C. The zeolites were synthesized by conventional techniques and characterized by XRD, pyridine FTIR and N2 adsorption. The adsorbed pyridine spectra demonstrated that new Lewis sites were formed after Zn exchange, and that the relationship between Lewis and Brönsted sites in the Zn-ZSM-11 zeolite (3.53) was much higher than that in the H-ZSM-11 zeolite (0.09). Thermal analyses confirmed that the temperature of decomposition of the polymer can be decreased in as much as about 145 °C when the catalysts were added. As compared to the thermal degradation, the catalytic conversion produced less solid residues and much higher amounts of gas and liquid hydrocarbons. The catalysts showed different yield profiles: the H-ZSM-11 zeolite yielded more gases, while the Zn-ZSM-11 zeolite yielded more liquid products. Notably over Zn-ZSM-11 zeolite, these liquid products were mainly aromatic, and depending on experimental conditions (higher temperature, longer reaction time, smaller polymer/catalyst relationship), aromatic selectivity could be increased to almost 100%.